Psychoanalysis Theory and Its Educational Implication - Pokhrel, Mohan Mani (Sotang, Yearly Peer Reviewed Journal, 2021)
This paper delves into the concepts of consciousness, sub-consciousness, and unconscious mind, as well as Id, ego, and superego levels of mind, defense mechanisms, and educational implications of Freudian theory. The main purpose of this paper is to introduce Freud's psychoanalytic theory and to search for the educational implications of psychoanalysis theory in the present Nepalese context. Freudian theory studies how potent inner forces of "libido" and psychic energy influence human behaviour. Two types of instincts: life instinct or sex/Eros and death instincts aggression/Thanatos, lead an individual's behaviour. This paper introduces psychosexual stages. The unconscious mind continues to influence human behavior, even though we are unaware of these underlying influences. Most activities are led by the unconscious mind, which are mostly stressful. It can be reduced by defense mechanisms.